Avaliação do uso de esquemas mentais no ensino da semiologia da dor torácica - Gema, Hector Jacques Rodrigues de Almeida Santa (2020)
Introduction: Clinical reasoning (CR) refers to the cognitive process through which the doctor is able to establish the correct diagnosis and propose an appropriate conduct concerning a certain clinical problem. Studies have been evaluating instructional methods to teach it. Learning based on the construction of disease presentation schemes has been suggested as an effective strategy, but its use has not been tested to support the development of CR. Although medical semiology is important to develop CR, in general, its teaching occurs separately from the practice of CR. Objectives: To evaluate the effect of teaching chest pain semiology through the construction of disease presentation schemes in the diagnostic accuracy of medical students. Materials and methods: Experimental study, carried out on medical students from 4th and 6th terms, in 3 phases. 26 students were recruited and randomly divided into 2 groups - SR and MM. Group SR versus Group MM, 4th term versus 6th term and study phases were compared. In the initial evaluation, students resolved 8 clinical cases which presented chest pain (CP). In the training phase, after a CP semiology mini-class, students were randomly divided into 2 groups, one of which was submitted to the teaching of CP semiology based on mind maps (MM), and the other used the structured reflection strategy (SR). After a week, students were submitted to an evaluation of 8 new cases with the same diagnoses. In all phases, the following were evaluated: the identification of the responsible organic system and of the structure responsible for the clinical manifestation, the diagnostic performance, the resolution time, and the participants' confidence in their answers. Results: In both groups there was an improvement in diagnostic performance, a reduction in the resolution time and an improvement in confidence in the diagnosis. There was not any difference in performance between Group SR and Group MM. The study revealed a strong correlation between identifying the anatomical structure involved in the manifestation of chest pain and a correct diagnosis. Conclusions: Both strategies were effective in teaching semiology and CR. The identification of the system and anatomical structure involved in the clinical presentation showed a strong correlation with the accuracy of the diagnosis